Neuroprotection by solanesol against ethidium bromide-induced multiple sclerosis-like neurobehavioral, molecular, and neurochemical alterations in experimental rats - Nidhi Sharma; Shubham Upadhayay; Ambika Shandilya; Rakesh Sahu; Anshuman Singh; Bidisha Rajkhowa; Sidharth Mehan (Elsevier, 2021)
Background: : Multiple Sclerosis (MS) is an idiopathic chronic neuroinflammatory disease characterized by neurodegeneration that clinically presents motor neuron disabilities, memory, and cognitive dysfunction. Recent findings suggest that the down-regulation of SIRT-1 associated with the progression of MS. Solanesol (SNL) is an active phytoconstituent isolated from the plant Nicotiana tobacum, belonging to the Solanaceae family and a significant biosynthetic precursor to CoQ10 with potent antioxidant and neuroprotective properties. Chemically, it is a long-chain non-cyclic terpene alcohol that consists of nine isoprene units. Purpose: : In the current study, we investigated the neuroprotective potential of SNL (40-80 mg/kg) in intracerebropeduncle (ICP) ethidium bromide (EB) induced MS-like neurobehavioral alterations in Wistar rats. Methods: : Wistar rats were equally divided into six groups (n = 6) and treated with 0.1%/10μl of ethidium bromide injection for seven days. Long-term treatment with SNL shows neuroprotective potential by improving motor function, grip strength, memory and cognition. Results: : Our findings are primarily related to the upregulation of SIRT-1 level and the myelin basic protein in the brain. In addition, SNL also modulates the level of apoptotic markers (caspase-3, Bax, Bcl-2) with mitochondrial-ETC complex dysfunction in the rat brain. Further, SNL decreased inflammatory cytokines (TNF-α, IL-1β), oxidative stress markers, and restored neurotransmitter levels. Our findings also reveal the neuroprotective effect of SNL by restoring gross pathological alterations and reducing the volume of demyelination in rats. Thus, the present study concludes that SNL as a SIRT-1 signaling activator has neuroprotective potential against EB-induced MS rats. Hence, SIRT-1 signaling may be an effective therapeutic target strategy for the treatment of MS. However, more investigations are needed to be carried out to prove these beneficial effects.